PENGARUH APLIKASI URINE SAPI TERFERMENTASI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (Lactuca sativa L) - Winahyu Dwi Novriansyah; Armaini Armaini; Rusli Rustam (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Lettuce (Lactuca sativa L) is one of the horticultural commodities which have commercial prospects and quite good. This study aimed determine the effect of application the best fermented cow urine concentration on growth and yield of lettuce plants. This research was conducted at the Experimental Farm, Faculty of Agriculture, University of Riau Campus Bina Widya Simpang Baru village Panam District of Tampan, Pekanbaru in October to December 2016. This study was conducted experimentally using RAL 5 treatments with 3 replications. The treatments were P1: POC cow urine concentration of 30%, Q2: POC cow urine concentration of 35%, P3: POC cow urine concentration of 40%, P4: POC cow urine concentration of 45% and P5: POC cow urine concentration of 50%. Data were analyzed statistically using analysis of variance followed by DNMRT at 5% level. The Parameters measured were plant height, leaf number, fresh weight and plant fresh weight unfit for consumption. The results showed that administration of fermented cow urine at a concentration of 45% indicates growth and better results on all parameters of lettuce plants and the use of cow urine concentration of 35% can be recommended to be applied. Keywords: Growth and yield, lettuce, POC fermented cow urine